Pengaruh lama perendaman dan penambahan susu skim terhadap karakteristik bubur kacang merah (Phaseolus vulgaris L.) instan: The effect of soaking time and skim milk on the characteristics of porridge flour of red kidney bean (Phaseolus vulgaris L.) instant - Palupi, Hapsari Titi; Afifah, Siti (TEKNOLOGI PANGAN : Media Informasi dan Komunikasi Ilmiah Teknologi Pertanian, 2023)
Phaseolus vulgaris L. are a type of legume that is potential and easily available in Indonesia. Processing red kidney beans into instant porridge is an effort to increase the usability of red kidney bean-based products. The purpose of this study was to determine the effect of soaking time of red beans and addition of skim milk to instant red kidney bean porridge based on physicochemical and organoleptic analysis. The research design used in this study is RAK (Group Random Design) consisting of two factors, factor 1: soaking time (12%, 24%, 36%), factor 2: concentrations of skim milk (5% and 10%). The parameters observed are moisture content, ash, protein content, phytic acid, water absorption, swelling, and solubility and organoleptic properties of color, taste, texture, and aroma. The data obtained were analyzed using ANOVA (Analysis of variance) with Tukey's follow-up test 95% confidence level (Î±<0.05). While sensory tests are carried out with the Friedman Test with a hedonic scale. The results of this study indicate that variations of soaking time and concentrations of skim milk have a significant impact on physicochemical and organoleptic properties are moisture content, ash, phytic acid, protein, water absorption, swelling, solubility, organoleptic parameter (color, texture, and aroma). The best treatment according to the results of physicochemical and organoleptic analysis tests is soaking time 36 hours and concentrations of skim milk 10%, with physicochemical and organoleptic analysis parameters including moisture content 4.28%, ash 1.53%, protein content 8.58%, phytic acid 3.08%, water absorption 5.08%, swelling 568.74%, solubility 29.92%, and organoleptic taste 4.56 (very like), color 4.52 (like), texture 4.60 (very like), and aroma 4.24 (like).